2012
DOI: 10.1089/tmj.2012.0041
|View full text |Cite
|
Sign up to set email alerts
|

Telepsychiatry Services for Korean Immigrants

Abstract: Asian Americans often face cultural and language barriers when obtaining mental health treatment. With the small number of Asian mental health providers, it is difficult to ensure the linguistic and ethnic matching of providers and patients. Telepsychiatry holds great promise to address the unique needs of Asian Americans. We developed a project to establish telepsychiatry services that connect Korean mental health patients in Georgia with a linguistically and culturally competent psychiatrist in California an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
68
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
4
3
2

Relationship

0
9

Authors

Journals

citations
Cited by 55 publications
(68 citation statements)
references
References 9 publications
0
68
0
Order By: Relevance
“…A recent study of nearly 40 rural health clinics compared impressions of 25 primary care providers (PCPs) and 32 staff impressions of factors important to care: using providers who value differences (5.4 and 7.0, respectively), quality of the provider's care (4.9 and 7.0, respectively), access to care in general (4.5 and 7.0, respectively), and availability of trained interpreters for use with patients (4.4 and 7.0, respectively). 38 Others are studying the specific needs of Hispanics/Latinos, 37,39,40 Asians, 41 Native Americans, 35,43,44 Eastern Europeans, 44 and those using sign language 45 -all using telepsychiatry for service provision. With patients of different cultural backgrounds, using the patients' primary language allows for a more comfortable atmosphere where they may express their genuine feelings and emotions.…”
Section: Specific Populations: Child Geriatric and Those Of Culturementioning
confidence: 99%
“…A recent study of nearly 40 rural health clinics compared impressions of 25 primary care providers (PCPs) and 32 staff impressions of factors important to care: using providers who value differences (5.4 and 7.0, respectively), quality of the provider's care (4.9 and 7.0, respectively), access to care in general (4.5 and 7.0, respectively), and availability of trained interpreters for use with patients (4.4 and 7.0, respectively). 38 Others are studying the specific needs of Hispanics/Latinos, 37,39,40 Asians, 41 Native Americans, 35,43,44 Eastern Europeans, 44 and those using sign language 45 -all using telepsychiatry for service provision. With patients of different cultural backgrounds, using the patients' primary language allows for a more comfortable atmosphere where they may express their genuine feelings and emotions.…”
Section: Specific Populations: Child Geriatric and Those Of Culturementioning
confidence: 99%
“…Telepsychiatry review consist of similar items rated on a Likert-scale. Of the 31 studies reviewed, 23 concluded that patients rated their experience with telepsychiatry services as "good" to "excellent" , while the remaining 7 studies reported mixed reactions among participants [29][30][31][32][33][34][35][36][37][38] . For example, Hilty et al [33] reported generally high satisfaction among outpatients seeking specialty mental health care but satisfaction scores were statistically higher for rural patients compared to suburban patients.…”
Section: Patient Satisfactionmentioning
confidence: 99%
“…Hilty et al (2013) found in their 2013 review of telemental health that such services were effective in providing both linguistically and culturally sensitive services to ethnic minorities. Ye et al (2012) saw the effectiveness of telepsychiatry services for Korean migrants living in a more remote area of the USA who received mental health care via computer-based videoconferencing technology from Korean mental health professionals working in a more urban area of the USA.…”
Section: Discussionmentioning
confidence: 99%